Effect of cutting height on the chemical composition, nutritional value and yield, fermentative quality and aerobic stability of corn silage and relationship with plant maturity at harvest. (December 2013) - Aoki, Yasuhiro; Oshita, Tomoko; Namekawa, Hiroaki; Nemoto, Eiko; Aoki, Mari
Abstract The experiment was carried out to investigate the effects of cutting height at harvest on the nutritional and fermentative properties and yield per unit area of corn (Zea mays L.) silage in relation to the maturity of the corn plants at the time of harvest. Corn forage at the early or late dent stage was harvested at normal (30 cm) or high (78 cm) heights. After the yield of fresh matter and dry matter per ha was recorded, whole‐crop corn silage was prepared. After 60 days of the ensiling, the samples were collected to examine the chemical composition, whole‐tract digestibility, fermentative quality and aerobic stability. Whole‐tract digestibility was determined by total fecal collections using wether sheep, and total digestible nutrition (TDN) was calculated. The yield per ha was also expressed on a TDN basis. We found that silage from corn harvested at the high cutting height contained significantly less neutral detergent fiber (NDF), acid detergent fiber (ADF) and acid detergent lignin. There was a significant interaction between cutting height and maturity for starch content; it increased for the high cutting height only in silage from corn harvested at the early dent stage, but did not exceed those levels in corn harvested later. The nitrate‐nitrogen content was significantly lower in corn silage harvested at high cutting height. Cutting at a higher level increased NDF and ADF digestibility and it could cause the significantly higher TDN content. The loss of nutritional yield per unit area due to high cutting was much less when corn forage was harvested at a later stage. No adverse effect on fermentative quality and aerobic stability was observed due to high cutting. These results suggest that high cutting of corn plants at the late dent stage is useful for silage preparation.